Study of tungsten oxide effect on the performance of BaTiO3 ceramics - Slimani, Y.; Selmi, A.; Hannachi, E.; Almessiere, M. A.; Mumtaz, M.; Baykal, A.; Ercan, I. (Journal of materials science. Materials in electronics, 2019)
BaTiO 3 /(WO 3 ) x ceramics (where x = 0, 0.5, 1, 2 and 5 wt%) were prepared by solid state reaction. X-ray powder diffraction, scanning electron microscope, Fourier transform-infrared spectroscopy and ultraviolet–visible diffuse reflectance spectrophotometry were used to investigate the structure, morphology and optical properties, respectively. The electrical and dielectric properties were also performed for different synthesized ceramics. A pure phase was obtained for x = 0.5 wt% ceramic, nevertheless a secondary phase was detected for x ≥ 1 wt% ceramics. The grains size increases for x = 0.5 wt% ceramic and then reduces abruptly with further increasing WO 3 content. The increase of grains size and the absence of impurities were all efficient to enhance the dielectric properties. A suitable WO 3 content leads to obtain ceramics having high dielectric constant and low tangent loss, which is encouraging for radio frequencies and microwaves applications.